2020
DOI: 10.21203/rs.3.rs-36810/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic Determinants Of Clinical Phenotype In Hypertrophic Cardiomyopathy

Abstract: Background: Hypertrophic cardiomyopathy (HCM) is the most common inherited cardiovascular disease that affects approximately one in 500 people. HCM is a recognized genetic disorder most often caused by mutations involving myosin-binding protein C (MYBPC3) and β-myosin heavy chain (MYH7) which are responsible for approximately three-quarters of the identified mutations.Methods: As a part of the international multidisciplinary SILICOFCM project (www.silicofcm.eu) the present study evaluated the association betwe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…A cross-sectional study design does not allow monitoring of disease progression. However, disease progression and response to pharmacological and lifestyle intervention in HCM is subject to our separate ongoing longitudinal SILICOFCM study [14,40].…”
Section: Study Limitationsmentioning
confidence: 99%
“…A cross-sectional study design does not allow monitoring of disease progression. However, disease progression and response to pharmacological and lifestyle intervention in HCM is subject to our separate ongoing longitudinal SILICOFCM study [14,40].…”
Section: Study Limitationsmentioning
confidence: 99%
“…MYH7 variants have been traditionally associated with an earlier onset, more severe LVH and higher incidence of SCD and arrhythmias, while MYBPC3 variants have been linked to later onset, slower disease progression and better prognosis [57,232–234]. Indeed, this notion has been supported by recent studies and meta‐analyses retrieving data from literature [235–237]. Different age onset has also been reported depending on the underlying sarcomere gene variant [236].…”
Section: Genetic Basis Of Hcmmentioning
confidence: 99%
“…To understand the incomplete penetrance and support early disease detection, researchers have been looking for environmental or genetic factors that modify the risk of disease manifestation. Typically, this research collects and analyzes phenotypical, environmental, and demographic information for carriers [8][9][10][11][12]. One very recent study by Verstraelen et al [13] used abnormalities observed in carriers to calculate the risk for malignant VA and guide the decision of when to start or withhold preventive therapies, including intracardiac defibrillators.…”
Section: Introductionmentioning
confidence: 99%